Chapter 19 Junk food marketing, childhood obesity, and the production of (un)certainty - Powell, Darren (Taylor & Francis, 2022)
The point of this chapter is to disrupt the 'truth' that food marketing contributes to childhood obesity by critically examining how certainty about this relationship is (re)produced through expert knowledge and the unquestioning acceptance of the 'junk food marketing = childhood obesity' discourse. My aim here is to illuminate how dominant obesity discourses work to produce 'regimes of truth' about the relationship between food marketing and childhood obesity; how expertise, power, knowledge, and discourses congeal and cohere to (re)produce the taken-for-granted assumption that junk food marketing = childhood obesity. In a similar vein to Gard and Wright's critique of 'certain' obesity discourses in physical education, my central concern is how scholars - particularly in the field of public health - contribute to the dismantlement of uncertainty (with respect to knowledge about the relationship between 'junk' food advertising and fatness) and the concomitant construction of certainty "where none seems justified".